Analysing inhibitors of integrating and routinizing Health Information Systems for Universal Health Coverage: the case of Cameroon - Nah, Flora; Sæbø, Johan Ivar (Journal of Health Informatics in Africa, 2017)
Background and Purpose: The purpose of this paper is to describe the state of HMIS in Cameroon, with particular emphasizes on the organisational factors affect integration, routinization and use of information for decision-making for the achievement of UHC goals. Methods: This paper is based on an interpretative case study on the implementation of electronic data-based in Cameroon. Data was collected through interviews conducted with District Health Managers, Facility Information Officers, and Matron-In-charge of healthcare facilities from December 2015, to January and July 2016. Document review was used as secondary data collection. Multiple variation sampling technique was used to select interviewees.Results: Though there is a “general expectation that as electronic IS (DHIS) has been implemented, computers and Internet dongles provided to district and facilities information managers, the quality of information generated will certainly become of good quality and could be used for decision making”. This assumption neither concurs with the perspective of ICTs for development nor ICT as an agent for institutional change. According to advocates for ICT as an agent for changes IS is an institution and in order for it to bring about change, all aspects (human and non-human, social, cultural and political factors) have to be given equal attention.This paper analysed inhibitors of HMIS integration in Cameroon. Factors that affect effective routinzing, integrating and use of HMIS are; multiple data collecting tools, centralized information management, inadequate information system infrastructure, lack of IT specialist and basic computer skills and non-culture of information use.Conclusions: HMIS offers a remarkable potential for improving the efficacy and effectiveness for healthcare and also for achieving the goal of UHC. However, its integration, routinization and use are quite variable depending on the context.